CO1 barcodes resolve an asymmetric biphyletic clade for Diabrotica undecimpunctata subspecies and provide nucleotide variants for differentiation from related lineages using real-time PCR - Tembrock, Luke R.; Wilson, Christina R.; Zink, Frida A.; Timm, Alicia E.; Gilligan, Todd M.; Konstantinov, Alexander S.; Tishechkin, Alexey K. (Frontiers in Insect Science, 2023)
Diabrotica undecimpunctata is a multivoltine polyphagous beetle species that has long been documented as a significant agricultural pest throughout its native range in North America. This beetle can vector bacterial and viral plant pathogens that result in major losses to crops such as cucumber and soybean. Many countries outside the Americas treat D. undecimpunctata as a species of quarantine importance, while in the USA only the subspecies D. u. duodecimnotata is subject to quarantine, to prevent introduction from Mexico. Identification of D. undecimpunctata on the basis of morphology alone can be complicated given the use of conflicting characters in the description of some subspecific taxa. To better understand relationships among D. undecimpunctata subspecies and other related species, we sequenced mitochondrial cytochrome oxidase 1 (CO1) and nuclear internal transcribed spacer 2 (ITS2) DNA from individuals in different subspecific taxa and across different parts of the species range using museum samples and interceptions. When our data were combined with publicly available Diabrotica data, no pattern of divergence consistent with the currently recognized subspecific designations was found. In addition, we compared phylogenetic patterns in CO1 data from the congener D. virgifera to demonstrate the utility of mitochondrial data in resolving subspecies. From the CO1 data, a diagnostic real-time PCR assay was developed that could successfully identify all haplotypes within the large D. undecimpunctata clade for use in surveys and identification at ports of entry. These findings underscore the need to resolve molecular and morphological datasets into cogent, lineage-based groupings. Such efforts will provide an evolutionary context for the study of agriculturally important attributes of Diabrotica such as host preferences, xenobiotic metabolism, and natural and anthropogenic patterns of dispersal.